Bilateral phacoemulsification of cataract: the opinion of foreign ophthalmologists - I. B. Medvedev; D. F. Pokrovsky (Российский офтальмологический журнал)
Рurpose: to present the opinion of foreign ophthalmic surgeons on simultaneous bilateral phacoemulsification of cataract (SBPEC) by analyzing literature data. We performed an analysis of papers listed by Pubmed in 2000–2020 which contained expert assessments of SBPEC effectiveness based on polling. Ophthalmic surgeons were offered special questionnaires largely close in content, which were designed to establish the rating of factors that affected the respondents’ decision for or against the surgery. Our results indicate that, depending on the country, from 13.9 to 86 % of ophthalmic surgeons practice SBPEC, while from 14.0 to 67.2 % refrain from using this technology. The surveys revealed three major factors in favor of SBPEC — reduced number of clinical visits, the patient’s convenience during rehabilitation, and a high risk of complications after a second general anesthesia. The main factors against SBPEC are the risk of endophthalmitis (noted by 69–73 % of respondents), the absence of information on the postoperative refractive result in the first eye, which could determine the choice of the intraocular lens on the second eye (74–80 %), the risk of bilateral vision loss (73–79 %), as well as possible forensic problems (52–58 %).Conclusion. The surveying highlights certain negative factors that need to be overcome in order for SBPEC to become more widespread. Raising the awareness of SBPEC practice and approval by the ophthalmic community is essential for a sustainable culture change regarding this technology. To achieve this aim, standardization of the SBPEC procedure is needed, followed by the development of training manuals and protocols for surgical intervention.